Vaccine development against tuberculosis before and after Covid-19 - Kaufmann, Stefan H. E. (Frontiers in Immunology, 2023)
Coronavirus disease has not only shaped the awareness of the impact of infectious diseases on global health. It has also provided instructive lessons for better prevention strategies against new and current infectious diseases of major importance. Tuberculosis (TB) is a major current health threat caused by Mycobacterium tuberculosis (Mtb) which has claimed more lives than any other pathogen over the last centuries. Hence, better intervention measures, notably novel vaccines, are urgently needed to accomplish the goal of the World Health Organization to end TB by 2030. This treatise describes how TB vaccine R&D can benefit from the Covid-19 vaccine pipeline from research to clinical development and where the TB field has to pursue its own ways. It begins with a brief discussion of major vaccine platforms in general terms followed by a short description of the most widely applied Covid-19 vaccines. Next, different vaccination regimes and particular hurdles for TB vaccine R&D will be described. This specifically considers the complex immune mechanisms underlying protection and pathology in TB which involve innate as well as acquired immune mechanisms and strongly depend on fine tuning of the response. A brief description of the TB vaccine candidates which have entered clinical trials follows. Finally, experiences from the Covid-19 vaccine R&D and rollout will be applied to the TB vaccine pipeline emphasizing similarities and dissimilarities.